Improving wellbeing and self-efficacy by social prescription. Issue 3 (March 2015) - Morton, L.; Ferguson, M.; Baty, F.
Highlights: Social Prescribing links patients in the Primary Care setting with non-medical sources of community support. The authors report the findings from an evaluation of the clinical effectiveness of a Social Prescribing initiative. The initiative was developed in partnership between a Mental Health Psychology Department and a Council's Cultural Partnerships Team. A series of free courses were offered to clients with mild to moderate mental health difficulties. Finding indicate this approach can contribute to improvement in well-being, Self Efficacy and a reduction in anxiety and depression.